The first pharaohs : their lives and afterlives - Dodson, Aidan, 1962- (The American University in Cairo Press, 2021)
"The five centuries that followed the unification of Egypt around 3100 BC-the first three dynasties--were crucial in the evolution of the Egyptian state. During this time all the key elements of the civilization that would endure for three millennia were put in place, centered on the semi-divine king himself. The First Pharaohs: Their Lives and Afterlives looks at what we know about the two-dozen kings (and one queen-regent), who ruled Egypt during this formative era, from the scanty evidence for the events of their reigns, through to their surviving monuments. It also considers how they were remembered under their successors, when some of the earliest kings' names were attributed to allegedly ancient ideas and events, and the ways in which some of their monuments became tourist attractions or were even wholly repurposed. Aidan Dodson recounts how two centuries of modern scholarship have allowed these rulers to emerge from an oblivion so total that some archaeologists had come to doubt their very existence outside the works of ancient chroniclers. Then, within a decade at the end of the nineteenth century, archaeological discoveries revealed a whole series of tombs and other monuments that not only confirmed these rulers' existence, but also showcased the skills of Egyptian craftsmen at the dawn of history"--